Historical Perspective: How the Discovery of HPV Virus Led to the Utilization of a Robot - Morand, Grégoire B.; Sultanem, Khalil; Mascarella, Marco A.; Hier, Michael P.; Mlynarek, Alex M. (Frontiers in Oral Health, 2022)
The treatment of oropharyngeal cancer has undergone many paradigms shifts in recent decades. First considered a surgical disease, improvements in radiotherapy led to its popularization in the 1990s. Subsequently, the discovery of the human papillomavirus (HPV) in the pathogenesis of oropharyngeal cancer, as well as the increase in HPV-associated oropharynx cancer incidence, have prompted a reevaluation of its management. Its sensitivity to standard treatment with a favorable prognosis compared to non HPV-associated oropharyngeal cancer led to a focus on minimizing treatment toxicity. Advances in radiation and surgical techniques, including the use of transoral robotic surgery, gave the rationale to ongoing de-escalation clinical trials in HPV-associated oropharynx cancer.